2014
DOI: 10.1155/2014/696403
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception of Rectosigmoid Colon Cancer Mimicking a Pedunculated Tumor

Abstract: Intussusception in adults is a rare phenomenon involving the colon in approximately 20% of cases. A 65-year-old man was hospitalized with anorexia, anemia, dehydration, and melena. Digital rectal examination revealed a palpable mass approximately 5 cm from the anal verge. The mass moved between the rectosigmoid colon and the rectum below the peritoneal reflection during radiographic examinations and during sigmoidoscopy. We strongly suspected a rectosigmoid pedunculated tumor and performed a low anterior resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The duration of symptoms is longer in enteric and benign lesions than in malignant and colonic ones [ 13 ]. In our case, intussusception of the sigmoid colon into the rectum is was secondary to a colonic lipoma, however a review of the literature demonstrated that, other lesions in the sigmoid wall are more likely to cause intussusception, such as sigmoid polyp [ 11 ], a sigmoid adenocarcinoma [ 14 , 15 ] and a sigmoid liposarcoma [ 12 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The duration of symptoms is longer in enteric and benign lesions than in malignant and colonic ones [ 13 ]. In our case, intussusception of the sigmoid colon into the rectum is was secondary to a colonic lipoma, however a review of the literature demonstrated that, other lesions in the sigmoid wall are more likely to cause intussusception, such as sigmoid polyp [ 11 ], a sigmoid adenocarcinoma [ 14 , 15 ] and a sigmoid liposarcoma [ 12 ].…”
Section: Discussionmentioning
confidence: 92%
“…Its sensitivity ranges from 71.4% to 87.5%, with a specificity neighboring 100% [ 9 ]. The characteristics of intussusception on CT are the ‘target’ or ‘sausage-shaped’ soft tissue mass, mesenteric vessels within the bowel lumen are also typical [ 6 , 13 , 14 ]. Moreover, complications of intussusception such as acute obstruction or bowel ischemia and etiologies of intussusception can also be diagnosed by CT.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the diverse presentation of symptoms, and that we cannot always see the characteristic images of intussusception in imaging test during the preoperative stage, the intussusception preoperative diagnostic rate is only 40-50% [2,7]. Abdomen x-ray usually reveals signs of bowel obstruction; on the ultrasonography, the characteristic intussusception image is a hyperechogenic concentric double halo finding along with thickening of the intestine wall [7,13].…”
Section: Discussionmentioning
confidence: 99%
“…Although intussusception was first described by Paul Barbette as a proximal bowel invagination to a distal portion, it was John Hunter who coined the term "intussusception" in 1789 by describing three patients with such findings [1]. Presently it is defined as telescoping of a proximal segment of the gastrointestinal tract into a distal segment and it occurs when an organic lesion of the bowel functions as a guiding point and it is pulled towards a distal segment due to normal peristalsis [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation